Attitudes of Graduate Students Towards Online Learning Systems - Sah, Hari Narayan (Janajyoti Journal, 2025)
Background: This study aimed to investigate graduate students’ attitudes toward online learning systems in theKathmandu Valley. With the growing reliance on digital platforms in education, understanding student perceptions is important for improving the effectiveness of online learning. Methods: A descriptive survey design was employed to collect data from 400 graduate students, comprising 250 from colleges in Kathmandu and 150 who completed the survey via google forms. A questionnaire containing 20 positive and negative statements, rated on a 5-point Likert scale, along with two open-ended questions, was used. Statistical tools, including the mean, standard deviation, t-test, chi-square test, and percentage analysis, were applied. Results: The findings revealed that most students had a positive attitude toward online learning systems, particularly recognising their usefulness in enhancing learning performance and supporting self-learning. However, challenges such as slow and unstable internet, limited digital literacy, and discomfort with screen- based learning negatively impacted the experiences of some students. No significant differences were found in attitudes based on gender or faculty. Conclusion: While student attitudes are generally favourable, the study highlights the need for improved internet infrastructure, digital literacy training, and integration of online learning concepts into the curriculum. Policymakers and educators should prioritise teacher training to enhance online education systems.